(untitled) (Current Problems in Rail Vehicles, 2021)
In this article are described partial results of analysis of the dynamic behaviour of two-section coach with common 3-axle bogie. The analysis is focused on running stability at higher speeds, compatibility with bridges, lateral dynamics in curve transition and forces caused in wheel–rail contact.